Impact of Digital HR Transformation on Employee Resilience: Unpacking the Conditional Indirect Effects of Employee Exploration and AI Trust - Muhammad Sajjad (Policy Journal of Social Science Review, 2025)
The manufacturing industry is going through technological disruption due to high influx of AI in this sector. Despite adoption of digital transformation in HR, the psychological and behavioral impact on employees are still underexplored. This study investigates the impact of digital transformation on employees resilience with indirect effects of employees exploration and AI trust in the manufacturing firms of Pakistan. Grounded on the conservation of resource theory and social cognitive theory, this study proposed a moderated mediated research framework where employee exploration mediates the relationship of digital transformation and employee resilience and AI trust act as the moderator in the relationship between employee exploration and employee resilience. The study uses the quantitative, cross section survey design where data was collected from 350 employees working in the manufacturing sector of Pakistan. The responses were gathered using a structured questionnaire which was based on well validated and authenticated established scales. Reliability and validity of the constructs were checked through Cronbach’s alpha, composite reliability and through confirmatory factor analysis while structural modeling was run using smart pls. The findings of study revealed that digital transformation significantly and positively influenced the employee resilience in the manufacturing firms of Pakistan. Furthermore, the indirect effect of employee exploration also mediates the relationship of digital transformation and employee resilience. However, this mediation is the partial mediation. In addition, AI trust also successfully moderates and strengthens the relationship of employee exploration and employee resilience. The overall model is best with respect to direct and indirect impact on employee resilience. The model is good fit and digital HR transformation process successfully predict the employee resilience explained through employee exploration in the presence of AI trust. The study has practical implications in the manufacturing of Pakistan where digital HR transformation should be embraced for cultivating the workforce adaptability and psychological robustness to leverage the AI enabled HR systems. Keywords: Digital HR Transformation, Employee Exploration, AI Trust, Employee Resilience, Manufacturing, Conservation of Resource Theory, Moderated Mediation